Event Monitoring and Evaluation by Community Pharmacists in Japan: A Pilot Study on Fenofibrate and Pemafibrate - Takahashi, Masao; Ooba, Nobuhiro; Nagamura, Marina; Ushida, Makoto; Kawakami, Eiji; Kimura, Masaomi; Sato, Tsugumichi; Takahashi, Yoshinori; Tokuyoshi, Junichi; Hashiba, Hajime; Kamei, Miwako; Miyazaki, Choichiro; et al. (Current Drug Safety, 2022)
Background: The Japan Pharmaceutical Association has conducted drug event monitoring to detect drug events related to pemafibrate. As there are a few studies on the safety of pemafibrate in clinical settings, a pilot study evaluating the association between drug use and detected events was performed in Japan. Aims: In this study, the association between detected events and the use of pemafibrate, utilizing pharmacy records maintained by community pharmacists, was investigated. We identified the newuser cohort using a test and active comparison drug and collected the baseline information. An active comparison group comprising new users was used to assess the events. Methods: A retrospective cohort study using questionnaires regarding baseline and event data was conducted by community pharmacists belonging to the Japan Pharmaceutical Association. The incidence of event and estimated hazard ratio were calculated using the Cox proportional hazards model that was adjusted for confounding factors, such as age and sex. Results: A total of 1294 patients using pemafibrate and 508 patients using fenofibrate were identified as new drug users. The most reported events involving suspected adverse reactions and add-on drugs were increased blood pressure and lipid-lowering effects with pemafibrate use, and nasopharyngitis, pruritus, dizziness, and lipid-lowering effects with fenofibrate use. No significant differences were found in commonly occurring events, except that an add-on anti-hypertensive drug has been used by pemafibrate users compared to fenofibrate users. Conclusion: This study conducted by pharmacists can facilitate the safety assessment of newly marketed drugs, as few drug use investigations with a comparator are carried out by the Japanese authority for pharmaceutical companies. However, further research is required.
Keywords: community pharmacist